2006
DOI: 10.1063/1.2188028
|View full text |Cite
|
Sign up to set email alerts
|

Electrical pulse formation during high temperature reaction between Ni and Al

Abstract: Articles you may be interested inThe role of microstructure refinement on the impact ignition and combustion behavior of mechanically activated Ni/Al reactive composites A new experimental setup for the time resolved x-ray diffraction study of self-propagating high-temperature synthesis Rev. Sci. Instrum. 73, 422 (2002);An electric voltage pulse ͑duration of about 2 ms͒ with an amplitude of up to 0.6 V was generated during the reaction between nickel and aluminum powders by a high temperature moving reaction f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 24 publications
0
7
0
3
Order By: Relevance
“…Another interesting activity conducted by this group is focused on spontaneous magnetization generated by solid state combustion [222][223][224][225][226][227][228]. Using a highly sensitive high-T c superconducting quantum interference device (SQUID), they were able to conduct the first measurement of the very low intensity (order of nT) transient magnetic field formed by a combustion front motion.…”
Section: Combustion Synthesis Research In Usa After 1980mentioning
confidence: 99%
“…Another interesting activity conducted by this group is focused on spontaneous magnetization generated by solid state combustion [222][223][224][225][226][227][228]. Using a highly sensitive high-T c superconducting quantum interference device (SQUID), they were able to conduct the first measurement of the very low intensity (order of nT) transient magnetic field formed by a combustion front motion.…”
Section: Combustion Synthesis Research In Usa After 1980mentioning
confidence: 99%
“…In all the experiments a small, short temperature drop occurred before the electric signal formed [12,13] . The initial increase in the heat release rate following ignition was not sufficient to compensate for the termination of the external heating by the match and led to the transient temperature drop.…”
Section: Emf Measurement Resultsmentioning
confidence: 99%
“…Several experimental studies revealed that the high-temperature front propagation during the combustion synthesis of Record [ materials generated an electrical voltage and a residual magnetic field of up to 1.5 V and 10 µT, respectively [7][8][9][10][11][12][13][14][15][16] . At present time mechanism was no established, which explains the generation of the temporal electric fields and spontaneous magnetization during the combustion of either ferromagnetic or nonferromagnetic materials.…”
Section: Introductionmentioning
confidence: 99%
“…Как было показано ранее, возникновение разности потенциалов в прекурсорах или генерирование электрических зарядов при получении наноразмерных оксидных, сложнооксидных и др. материалов в реакциях самораспространяющегося высокотемпературного синтеза (СВС) [1][2][3][4][5][6][7] и горения органо-неорганических композиций [8][9][10][11][12] происходит из-за различной подвижности носителей зарядов разного знака при движении фронта горения либо вследствие уноса в газовую среду заряженных частиц газообразных продуктов горения. В первом случае отмечена разность потенциалов величиной, составляющей доли вольта [1][2][3][4][5][6][7][13][14][15][16].…”
Section: Introductionunclassified
“…материалов в реакциях самораспространяющегося высокотемпературного синтеза (СВС) [1][2][3][4][5][6][7] и горения органо-неорганических композиций [8][9][10][11][12] происходит из-за различной подвижности носителей зарядов разного знака при движении фронта горения либо вследствие уноса в газовую среду заряженных частиц газообразных продуктов горения. В первом случае отмечена разность потенциалов величиной, составляющей доли вольта [1][2][3][4][5][6][7][13][14][15][16]. При горении органо-неорганических прекурсоров, например, полимерносолевых (нитратсодержащих) композиций, разность потенциалов между прекурсором или твердофазными продуктами синтеза и землей, начиная от долей вольта, может достигать сотен вольт, что соответствует зарядам высокой плотности [8][9][10][11][12].…”
Section: Introductionunclassified